ISOTOPE GEOCHEMISTRY (O, C, S, SR) AND RB-SR AGE OF CARBONATITES IN CENTRAL TUVA - Nikiforov A.V.; Bolonin A.V.; Chugaev A.V.; Lykhin D.A.; Pokrovsky B.G.; Sugorakova A.M. (My University, 2006)
The Rb-Sr isochron age of igneous ankerite-calcite and siderite carbonatites in central Tuva is estimated at 118 ± 9 Ma. The following ranges of initial values of O, C, Sr, and sulfide and S isotopic compositions were established: δ18 Ocarb = +(8.8-14.7)‰, δ13 Ccarb = -(3.6-4.9)‰, δ18 Oquartz = +(11.6-13.7)‰, δ34 Spyrite = +(0.3-1.1)‰, and (87 Sr/86Sr)i =0.7042-0.7048 for ankerite-calcite carbonatite and δ18Osid = +(9.2-12.4)‰, δ13Csid = -(3.9-5.9)‰, δ18Oquartz = +(11.2-11.4)‰, δ34Spyrite = -(4.4-1.8)‰, δ34Ssulfate = +(8.6-14.5)‰, and (87Sr/86Sr)i = 0.7042-0.7045 for siderite carbonatite. The obtained isotopic characteristics indicate that both varieties of carbonatites are cognate and their mantle source is comparable with the sources of Late Mesozoic carbonatites in the western Transbaikal region and Mongolia. The revealed heterogeneity of isotopic compositions of carbonatites is caused by their contamination with country rocks, replacement with hydrothermal celestine, and supergene alteration. © Pleiades Publishing, Inc. 2006.
Keywords: Mesozoic; Mesozoic; Мезозой